Sex differences among endurance athletes in the pre-race relationships between sleep, and perceived stress and recovery. Issue 14 (18th July 2022) - Roberts, Spencer S.H.; Main, Luana C; Condo, Dominique; Carr, Amelia; Jardine, William; Urwin, Charles; Convit, Lilia; Rahman, Shant S; Snipe, Rhiannon M.J.
ABSTRACT: This study examined sex differences among endurance athletes in pre-race relationships between sleep, and perceived stress and recovery. Thirty-six athletes completed the Short Recovery and Stress Scale, and had sleep monitored via actigraphy, over four consecutive days prior to an ultra-marathon. Overall, compared with males, females had shorter wake after sleep onset (mean ± SD, 50 ± 23 vs 65 ± 23 min, p = .04) and lower emotional balance (3.9 ± 1.1 vs 4.8 ± 1.1 arbitrary units, p = .001). The day before the race, females scored higher for all stress-related items ( p < 0.05). Among females, higher scores for emotional balance (β = −31 min, p = .01) and negative emotional state (β = −21 min, p < .001) were associated with reduced sleep duration. Among males, higher scores for overall stress were associated with increased sleep duration (β = 22 min, p = .01). Across all athletes, longer sleep duration was associated with improved overall recovery (β = 0.003 arbitrary units, p = .02). Females experienced greater pre-race stress than males, and their sleep duration was associated with emotional factors. The SRSS may help identify female athletes at risk of sleep difficulties prior to competition.